Taxinomia e mitose de célula haplóide em Nothoscordum fragrans (Vent.) Kunth - Shimoya, Chotaro (Revista Ceres, 2025)
This paper consists of an external mosphological description of vegetative and reproductive organs, as well as the description of the first mitosis of microspores, of wild garlic, Nothoscordum fragrans (Vent.) Kunth. The anthers of this species constitute good material for studies of mitotic stages, morphology and numerical counts of chromosomes, which are large and 9 in number. The mitosis is rapid and all the stages of division are found in the same anther. Floral buds, about 3 mm in length, were collectes in March, between noon and 2p.m. The anthers were smeared by carmine-acetic method.